2020
DOI: 10.5505/ejm.2020.81905
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary thrombophilia risk factors in patients with venous thromboembolism

Abstract: Venous thromboembolic disease (VTD) is a serious cause of mortality and morbidity with an incidence of 0.1% per year. The etiology of VTD is multifactorial and associated with acquired and hereditary conditions. The aim of our study was to investigate the presence of rare genetic mutations in VTD patients and to evaluate their distribution according to thrombosis sites. The study group consisted of 107 patients who underwent genetic testing for thrombophilia due to VTD between 2015 and 2017. Patients with VTD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Though MTHFR A1298C has not been shown to affect the enzyme's function and subsequent homocysteine levels, research is conflicting regarding MTHFR's possible association with a prothrombotic condition. Some studies found that the MTHFR A1298C polymorphism was significantly more common in patients with deep vein thrombosis than controls [11], while others found that neither MTHFR C677T nor A1298C was significantly associated with deep vein thrombosis [12], only MTHFR C677T is associated with thrombosis [13], or that either variant is associated with thrombosis but only when present with factor V Leiden [14]. Thus, further research is warranted to investigate the possible association of the different MTHFR variants with incidences of thromboses, with and without other genetic hypercoagulable states and risk factors, as well as in association with homocysteine levels.…”
Section: Discussionmentioning
confidence: 99%
“…Though MTHFR A1298C has not been shown to affect the enzyme's function and subsequent homocysteine levels, research is conflicting regarding MTHFR's possible association with a prothrombotic condition. Some studies found that the MTHFR A1298C polymorphism was significantly more common in patients with deep vein thrombosis than controls [11], while others found that neither MTHFR C677T nor A1298C was significantly associated with deep vein thrombosis [12], only MTHFR C677T is associated with thrombosis [13], or that either variant is associated with thrombosis but only when present with factor V Leiden [14]. Thus, further research is warranted to investigate the possible association of the different MTHFR variants with incidences of thromboses, with and without other genetic hypercoagulable states and risk factors, as well as in association with homocysteine levels.…”
Section: Discussionmentioning
confidence: 99%
“…Other Turkish study demonstrated that there was no significant impact on pulmonary embolism by single mutation of MTHFR (27). Another recent study in 2020 revealed that there was no significant difference in C677T MTHFR gene with venous thromboembolism (% of mutational in patients group was 57% versus 48.2% in control group) (28).…”
Section: Mthfr C677tmentioning
confidence: 96%